All our health … and inequalities. (2nd March 2020) - Webster, Lisa
Abstract : To celebrate the Year of the Nurse and Midwife, and to recognise the amazing work you do, we will be publishing a series of articles detailing some of your journeys. This month, Lisa Webster discusses nurses' role in reducing inequalities.